Novel trifluoromethylpyridine piperazine derivatives as potential plant activators - Zhang, Wei; Guo, Shengxin; Wang, Ya; Tu, Hong; Yu, Lijiao; Zhao, Zhichao; Wang, Zhenchao; Wu, Jian (Frontiers in Plant Science, 2022)
Plant virus diseases seriously affect crop yield, especially tobacco mosaic virus (TMV) and cucumber mosaic virus (CMV). The development of plant immune activators has been an important direction in the innovation of new pesticides. Therefore, we designed and synthesized a series of trifluoromethyl pyridine piperazine derivatives (A1-A27), and explored the action mechanism of active compound. The antiviral activity test showed that compounds A1, A2, A3, A9, A10, A16, A17 and A21 possessed higher activities than commercialized ningnanmycin. Particularly, the in vivo antiviral activity indicated that compound A16 showed the most potent protective activity toward TMV (EC50 = 18.4 μg/mL) and CMV (EC50 = 347.8 μg/mL), compared to ningnanmycin (50.2 μg /mL for TMV, 359.6 μg/mL for CMV). The activities of defense enzyme, label -free proteomic and qRT-PCR analysis showed that compound A16 could enhance the defensive enzyme activities of superoxide dismutase (SOD),polyphenol oxidase (PPO) and phenylalanine ammonialyase (PAL), and activate the phenylpropanoid biosynthesis pathway to strenthen the antiviral activities of tobacco. This study provides reliable support for the development of new antiviral pesticides and potential antiviral mechanism.